Incidence of Congenital Syphilis in Brazilian Geographic Regions, 2007-2016 - de Castro Monteiro Loffredo, Leonor; Telarolli Júnior, Rodolpho; Lian Sartore Segantini, Bruno; Wagner Maurencio, Christian; Santos Galego, Fabiano; Ramalho Borges, João; Eschaquetti Benevides, Társis (O Mundo da Saúde, 2020)
Congenital syphilis is an infectious and contagious disease, which is compulsory to report, and is associated with fetal and perinatal deaths, low birth weight and other sequelae. The objective of the study was to analyze the incidence of congenital syphilis in Brazil according to geographic region and year, in the period from 2007 to 2016. This was an epidemiological, an ecological and a time trend study with an exploratory purpose. The annual cases of congenital syphilis reported to SINAN (National System of Notifiable Diseases, Ministry of Health) and the number of live births were obtained according to the Live Birth Information System (SINASC, Ministry of Health) between 2007 and 2016 according to geographic region: North, Northeast, Midwest, Southeast and South. As this is a study that uses secondary data sources, underreporting births and diagnoses is its main methodological limitation. Incidence rates were calculated and presented in tables and graphs. The incidence of congenital syphilis in Brazil in the period from 2007 to 2016 was 3.97 per 1,000 live births, increasing significantly in the last five years (p <0.05), a tendency also verified by geographic region. The increase in congenital syphilis is worrisome, and may be due to poor quality prenatal care, the inadequate model of treatment for pregnant women and their partners, and the reduction of underreporting the problem. As appropriate measures to mitigate the impact of this public health problem, it is recommended that the coverage and quality of prenatal care increase, with early diagnosis and treatment of syphilis in pregnant women and their sexual partners, in addition to the monitoring of newborns.